2021
DOI: 10.3389/fmed.2021.641633
|View full text |Cite
|
Sign up to set email alerts
|

Rewarming From Hypothermic Cardiac Arrest Applying Extracorporeal Life Support: A Systematic Review and Meta-Analysis

Abstract: Introduction: This systematic review and meta-analysis aims at comparing outcomes of rewarming after accidental hypothermic cardiac arrest (HCA) with cardiopulmonary bypass (CPB) or/and extracorporeal membrane oxygenation (ECMO).Material and Methods: Literature searches were limited to references with an abstract in English, French or German. Additionally, we searched reference lists of included papers. Primary outcome was survival to hospital discharge. We assessed neurological outcome, differences in relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 145 publications
(134 reference statements)
1
8
2
Order By: Relevance
“…The majority of our hypothermic patients died due to asphyxia-related brain death within the first 3 days. A systematic review and meta-analysis including 464 patients reported a nearly double overall survival rate (37%) compared to our results [33]. This discrepancy could be due to the aetiology of hypothermia, as the mentioned review analysed a mixed population from 23 studies, whereas asphyxia-induced cardiac arrests (after avalanche burial and immersion) dominated in our work.…”
Section: Discussioncontrasting
confidence: 76%
“…The majority of our hypothermic patients died due to asphyxia-related brain death within the first 3 days. A systematic review and meta-analysis including 464 patients reported a nearly double overall survival rate (37%) compared to our results [33]. This discrepancy could be due to the aetiology of hypothermia, as the mentioned review analysed a mixed population from 23 studies, whereas asphyxia-induced cardiac arrests (after avalanche burial and immersion) dominated in our work.…”
Section: Discussioncontrasting
confidence: 76%
“…Extracorporeal cardiopulmonary resuscitation (ECPR) [ 139 ] followed by ECLS rewarming may be associated with higher survival and more favourable neurological outcomes than conventional CPR alone in patients with accidental hypothermia without vital signs [ 121 , 126 ]. Rapid technological progress including the miniaturisation and improved efficacy, safety, and transportability of ECLS devices are expanding the possibilities of ECPR and ECLS rewarming [ 122 , 140 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Avalanche victims have the lowest probability of surviving. Male sex, high initial body temperature, low pH, and high serum potassium were associated with decreased chances of survival [ 121 , 146 ].…”
Section: Treatmentmentioning
confidence: 99%
“…In fact, ECMO rewarming has been suggested to be superior to other ECLS techniques (Silfvast and Pettila, 2003 ). By using the ECMO technique for rewarming, the survival and neurologic outcome of accidental hypothermia patients with HCA has improved significantly (Debaty et al, 2017 ; Bjertnaes et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%